2021
DOI: 10.32637/orli.v50i2.361
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Head and Neck Cancer Patients at Hasan Sadikin Hospital in 2013-2018

Abstract: Background: Head and neck cancer (HNC) is the 6th highest cancer worldwide. Risk factors include history of smoking, exposure of carcinogen, diet, oral hygiene, HPV and EBV infections, genetic, and alcohol consumption. Purpose: To identify the profile of HNC patients in the Department of Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) Hasan Sadikin General Hospital Bandung from 2013 to 2018. Method: A retrospective descriptive study was conducted in 2013-2018 in the Department of ORL-HNS Hasan Sadikin Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…diagnosed with NPC often when there has been extensive tumor expansion and metastasis to the neck lymph nodes where there have been complaints of lumps in the neck at an advanced stage that caused delays from the treatment. 5,6,19 The performance status of patients assessed with ECOG before chemotherapy was in ECOG 1 status in 12 people (80%) and ECOG 2 in 3 people (20%). But slightly different from the results of research conducted by Xie, et al, in China in 2016 which got 47.46% in the status of ECOG performance 0-1 and 52.53% in the performance status of ECOG 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…diagnosed with NPC often when there has been extensive tumor expansion and metastasis to the neck lymph nodes where there have been complaints of lumps in the neck at an advanced stage that caused delays from the treatment. 5,6,19 The performance status of patients assessed with ECOG before chemotherapy was in ECOG 1 status in 12 people (80%) and ECOG 2 in 3 people (20%). But slightly different from the results of research conducted by Xie, et al, in China in 2016 which got 47.46% in the status of ECOG performance 0-1 and 52.53% in the performance status of ECOG 2.…”
Section: Discussionmentioning
confidence: 99%
“…At the H. Adam Malik Hospital Medan in 2014-2016, there were 396 patients with NPC, while in the Dr. Mohammad Hoesin Hospital Palembang there were 284 NPC patients from the period 2013-2017. [3][4][5][6][7] The immune system is the reaction of cells, tissues, and molecules that deliver and provide a coordinated immune response to pathogens, tumors, or other molecules that are considered foreign including tumor cells in NPC. There is a known immunoediting theory that encompasses the dynamic processes of immunosurveillance and tumor development that prevent malignancy by destroying tumor cells and keeping residual tumor cells dormant.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence in the age range of 50-54 years old was found to be 371 patients or about 12.57% of patients. 12 Handayani et al studied the prevalence of head and neck cancer at Dr. Hasan Sadikin General Hospital and reported that 34% of patients were in the age group of 41-50 years old. 13 c.…”
Section: Age Distributionmentioning
confidence: 99%
“…In Indonesia, the prevalence of NPC is 6.2/100,000 people, with around 13,000 new cases each year. NPC was the most frequent head and neck cancer in the Otorhinolaryngology-Head and Neck Surgery Department Dr. Hasan Sadikin Hospital Bandung from 2013 to 2018, with 921 (35.20%) new cases [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%